Strategi Promosi Paket Wisata PT Blutama Imawangi Tour and Travel Banyuwangi - Nurma Safitri; Masetya Mukti; Esa Riandy Cardias (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
PT Blutama Imawangi Tour and Travel is an industry that provides ticket sales, overseas packages and domestic tours. The problem that occurs at PT Blutama Imawangi Tour and Travel is the lack of effort in terms of promoting tour packages and sales of tour packages that fluctuate. The research location is at PT Blutama Imawangi Tour and Travel located at Jl. Gajah Mada, Palapa II No. 49 Banyuwangi. This study aims to analyze internal and external factors and formulate strategies that can be carried out on promotions at PT Blutama Imawangi Tour and Travel. The data were analyzed using descriptive qualitative methods obtained from observations, documentation and interviews with the selection of sources (owner, marketing department employees, customers) using purposive sampling techniques. The analysis used is the IE matrix and SWOT analysis. The results of this study show alternative promotion strategies, SO strategies, namely increasing promotion through social media and adjusting brochure content to public interests and following government programs and becoming a partner in tourism promotion. The WO strategy is to maximize the number of marketing employees and add new and unique tour packages. The ST strategy is to improve the quality of brochures and maintain cooperation with other agencies. The WT strategy is to develop promotions through social media that are not yet owned and to cooperate with other institutions that understand the promotion of their tour packages.